2020
DOI: 10.24843/ejmunud.2020.v09.i05.p14
|View full text |Cite
|
Sign up to set email alerts
|

Brand Awareness Memediasi Pengaruh Social Media Marketing Terhadap Keputusan Pembelian

Abstract: In order to stay in competition, Starbucks Coffee must be able to develop and innovate to determine an effective strategy. One of them is by using attractive social media marketing to builds brand awareness and leading to consumer purchasing decisions. The research objective is to determine the role of brand awareness mediating the effect of social media marketing on purchasing decisions. This research was conducted in Denpasar with 110 respondents through a purposive sampling method. Data collected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
3
13
1
3
Order By: Relevance
“…It can be interpreted that partially social media marketing what Kooka Coffee has done has a positive and insignificant effect on purchasing decisions made by Kooka Coffee consumers, so H1 is rejected. This result is not in line with research conducted by Upadana and Pramudana (2020), Narayana and Rahanatha (2020), as well as research from Purwaningsih and Susanto (2020) which shows social media marketing positive effect and significant to purchasing decisions. But the results in this study are in line with research conducted by Okadianiet al ( 2019) who found that social media marketing does not have a significant effect on purchasing decisions directly.…”
Section: Hypothesis Testingcontrasting
confidence: 85%
“…It can be interpreted that partially social media marketing what Kooka Coffee has done has a positive and insignificant effect on purchasing decisions made by Kooka Coffee consumers, so H1 is rejected. This result is not in line with research conducted by Upadana and Pramudana (2020), Narayana and Rahanatha (2020), as well as research from Purwaningsih and Susanto (2020) which shows social media marketing positive effect and significant to purchasing decisions. But the results in this study are in line with research conducted by Okadianiet al ( 2019) who found that social media marketing does not have a significant effect on purchasing decisions directly.…”
Section: Hypothesis Testingcontrasting
confidence: 85%
“…In line with previous studies whose research results state that brand awareness mediates the influence of social media marketing on buying decisions, which means that purchasing decisions are highly dependent on the level of brand awareness and also the level of social media marketing (Upadana & Pramudana, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…According to Upadana and Pramudana (2020), brand awareness is one of the results of branding. Brand awareness is a person's ability to remember or recognize a particular brand or product spontaneously or with specific keywords.…”
Section: Brand Awarenessmentioning
confidence: 99%